Financial Record Checking in Surveys: Do Prompts Improve Data Quality?. Issue 3 (August 2016) - Murphy, Joe; Rosen, Jeffrey; Richards, Ashley; Riley, Sarah; Peytchev, Andy; Lindblad, Mark
Self-reports of financial information in surveys, such as wealth, income, and assets, are particularly prone to inaccuracy. We sought to improve the quality of financial information captured in a survey conducted by phone and in person by encouraging respondents to check records when reporting on income and assets. We investigated whether suggestive prompts influenced unit response, compliance with the request to check records, precision of estimates, and accuracy. We conducted a split sample experiment in the Community Advantage Panel Survey in which half of telephone respondents and half of in-person household interview respondents were encouraged to check the records. We found a modest positive effect of prompts on compliance but no effect on unit response, precision, or accuracy.